2017
DOI: 10.1108/ijem-08-2016-0171
|View full text |Cite
|
Sign up to set email alerts
|

Developing relationships with school customers: the role of market orientation

Abstract: Purpose While the role of relationship marketing to consumers’ overall satisfaction with schools has been discussed in the education management literature, empirical studies on the marketing mechanisms that underpin school-customer relationships are limited. The purpose of this paper is to establish the association between market orientation (MO) in the school context and key relationship marketing performance indicators. Design/methodology/approach MO and four relationship constructs (brand trust, affective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 67 publications
(72 reference statements)
2
15
0
4
Order By: Relevance
“…In other terms, in the American context, not only does the trust construct represent a more significant factor leading to the establishment of supportive alumni-university long-term relations, but commitment also plays a more active role in the formation of alumni attitude toward donations. Therefore, these results allow us to corroborate and enrich the extant studies analysing the role of trust as an antecedent of student support (Ghosh et al 2001) as well as those examining the role of commitment as a factor leading to the formation of alumni attitude toward donations (Baruch and Sang, 2012;Jillapalli and Jillapalli 2014;Poole 2017).…”
Section: Discussion Of the Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…In other terms, in the American context, not only does the trust construct represent a more significant factor leading to the establishment of supportive alumni-university long-term relations, but commitment also plays a more active role in the formation of alumni attitude toward donations. Therefore, these results allow us to corroborate and enrich the extant studies analysing the role of trust as an antecedent of student support (Ghosh et al 2001) as well as those examining the role of commitment as a factor leading to the formation of alumni attitude toward donations (Baruch and Sang, 2012;Jillapalli and Jillapalli 2014;Poole 2017).…”
Section: Discussion Of the Resultssupporting
confidence: 72%
“…Previous literature (Johnson et al 2010;Poole 2017) has identified three different forms of commitment that a person can experience with an organisation: (1) affective commitment, related to the emotive connection towards the organisation;…”
Section: Commitmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on support from pertinent literature (Poole, 2017;Mokoena and Dhurup, 2016;Felgueira and Rodrigues, 2012;Niculescu et al, 2016;Zebal and Goodwin, 2012;Hemsley-Brown and Oplatka, 2010;Rivera-Camino and Ayala, 2010;Mitra, 2009;Hampton et al, 2009;Oplatka and Hemsley-Brown, 2007;Flavián and Lozano, 2006;Oplatka et al, 2002), the sample for present study is comprised of university teachers (and administrators) from five divergent, the largest and the oldest public sector universities of Sindh province, Pakistan, housing more than 50% of population of interest. Sindh is socio economically the most vibrant province, with the country's largest/well equipped sea port, hosting huge diversity of population from miscellaneous strata/clusters.…”
Section: Sample and Data Collectionmentioning
confidence: 99%